Survival with radical mastectomy for invasive breast cancer - Díaz, Juan (2015)
To compare the rates of long-term survival according to various clinical and pathological and therapeutic factors and determine the ten-year survival rates and recurrence after radical mastectomy classic (MRC) and modified radical mastectomy (MRM). MATERIALS AND METHODS: We retrospectively reviewed the medical records of 72 patients with operable invasive breast carcinoma with negative axilla (n = 38) or positive (n = 34), treated with MRC (n = 57) or MRM (n = 15) Belen Hospital, Trujillo, Peru, from 1 January 1966 to December 31, 1995. RESULTS: The mean age was 47.6 ± 9.5 years (range 30-70 years). The average disease duration was 9 months (range 0.3 to 156 months). The most frequent symptoms or signs were present tumor (100%) and breast (37.5%) pain. The ten-year survival rates in patients treated with MRC and MRM, according to the actuarial Kaplan-Meier method were 58% and 54%, respectively (p = NS). There was no significant difference in the rate of ten-year survival between the group of MRC and MRM considering tumor size, number of positive regional nodes, axillary committed, pathological stage and type of treatment. In patients with negative axillary lymph there was a significant improvement in the ten-year survival when treated with MRC with MRM (68% versus 38%, p <0.05). Decadal regional local recurrence rates, and distance MRC group were 21%, 1.8% and 24.6% respectively, while the MRM group decadal rates of local, regional and distant recurrence were 13 , 3 10% and 26%, 7%, respectively (p = NS). CONCLUSIONS: In patients with operable breast carcinoma, the ten-year survival is similar when they are treated with MRC and MRM; however in patients with negative axillary nodes, the ten-year survival is favorably influenced by the MRC.